Rapid monitoring system for the National Geodetic Vertical Datum (NGVD) - Mohd. Omar, Kamaludin (UTM, 2004)
Global Positioning System (GPS) technology was introduced in Malaysia in early 90s has changed the scenario of survey profesion rapidly. The current GPS infrastructure in Malaysia is mainly served as a ground control station for mapping and cadastral survey purposes. Precise height determination with GPS, needs a precise geoid model that can gives the geoid separation (N) at any location. With the airborne gravity survey conducted by Department of Survey and Mapping Malaysia (DSMM) being completed, the precise geoid will be widely used by the survey and mapping community for height determination compare to the conventional levelling. This study mainly focus on the theory of geoid fitting between gravimetric geoid and National Geodetic Vertical Datum (NGVD) that can produced the local precise geoid at the level of sub-centimeter . Analysis of the results has produced the working procedures for GPS Levelling with accuracy better than the conventional second order levelling. The results also shown that GPS Levelling can be used as a tools to monitor the current status of Bench Mark and establishing new levelling routes.